Participación del ministerio público dentro del proceso penal acusatorio (2014)
This paper through a reflective essay about the participation of the prosecutor in the accusatory penal system is developed, which is relevant to know what are the actions of this entity within the social context of the country are in each of the phases of this work is developed from a personal view of what is the participation of small legal entity and addressing data on the participation of the institution in the stages of accusatory penal system, where you will have in mind the differences Control between this body and the parts themselves the adversarial justice system, on the other hand it is important to note that there is now different positions on the participation of the Public Prosecutor in the criminal process and its relevance to the defense of fundamental rights of people